Multidrug-resistant Shigella infection in pediatric patients with diarrhea from central Iran - Abbasi, Elnaz (Infect Drug Resist, 2019)
Background: Shigella spp. are primary pathogens of diarrhea in children worldwide. Emergence of resistance to fluoroquinolones and third-generation cephalosporins is crucial in the management of pediatric shigellosis. We determined the prevalence and the antibiotic resistance patterns of Shigella species isolated from pediatric patients in central Iran. Materials and methods: Pediatric diarrhea samples (n=230) were cultured on MacConkey and XLD agar media and in GN broth. Genus-specific PCR for ipaH was also used for detection directly from fecal specimens. Antibiotic resistance and the frequency of ESBL and AmpC genes were determined. Results: Out of the 230 samples, 19 (8.2%) cases of Shigella spp. were identified using culture. Twenty-six samples were positive by PCR (11.3%), S. flexneri (4/19; 21%) and S. sonnei (15/19; 78.9%) being the most detected. The highest antibiotic resistance rates were found for cotrimoxazole (19/19; 100%), ampicillin (16/19; 84.2%), cefixime (13/19; 68.4%) and ceftriaxone (12/19; 63.1%). Ten cases showed phenotypic ESBL presence and all these strains were positive for bla(TEM), bla(CTX-M-1), and bla(CTX-M-15). Three strains were AmpC positive, all of which harbored bla(CMY-2) and two contained bla(CIT). Of the 19 Shigella isolates 5 (26.3%), 2 (10.5%), and 1 (5.2%) were phenotypically resistant to nalidixic acid, ciprofloxacin, and norfloxacin, respectively. Class 1 integron was found in 18 (94.7%) isolates whereas class 2 integron was found in 19 (100%) strains. Conclusion: We found a considerable presence of Shigella species with elevated antibiotic resistance levels. In particular, the resistance to third-generation cephalosporins (ESBL) and ciprofloxacin must be taken seriously.